Sustaining primary care teams in the midst of a pandemic - Sullivan, Erin E. (Isr J Health Policy Res, 2020)
The challenges wrought by the COVID-19 pandemic on health systems have tested primary care clinicians, who are on the front lines of care delivery. To ensure the longevity of the primary care workforce, strong interprofessional teams are one important solution to alleviating burnout and increasing clinician and patient satisfaction, but the pandemic has demonstrated that the operating manual needs to be adapted for virtual work. Essential principles of primary care, including preventative care, communication and collaboration, and building strong relationships, can be applied to strengthen virtual primary care teams.